Clinical cues for distinguishing bullous fixed drug eruption from Stevens–Johnson syndrome: A case report - Luna Samman; Chloe Fernandez; Victoria Dukharan; Patrick Dominguez (SAGE Open Medical Case Reports)
This case report discusses two clinical encounters of a 62-year-old Hispanic woman initially hospitalized with suspected Stevens–Johnson syndrome, later correctly diagnosed with bullous fixed drug eruption during an outpatient visit for a similar eruption. The first encounter involved an extensive evaluation and an 11-day hospital stay, while the second was managed successfully as an outpatient with oral prednisone. This report highlights the importance of differentiating bullous fixed drug eruption from Stevens–Johnson syndrome/toxic epidermal necrolysis and emphasizes the need for a collaborative approach between Primary Care Providers and Dermatology to ensure optimal patient care.